Working capital management and profitability : evidence from panel data analysis of random companies in Malaysia / Adelheid J Mianus - Mianus, Adelheid J (2015)
A massive exposure on working capital management opens up wider knowledge and application of working capital management towards the profitability of a firm. The objective of this research is to investigate the relationship of working capital components: current ratio, inventory turnover ratio and debt ratio towards the profitability of a firm. Using panel data analysis, for a sample of Malaysian firms from 2007 to 2011, we found that managers can increase profitability by managing their liquidity position efficiently. Data collections are random and are important to bring insight to conduct the research. The result and findings will be discussed for achieving goals of the research.